Momentos - Bravo, Ofelia; Bravo, Ofelia; Rodríguez M., Mayra; Ferreiro, Ricardo M.; Ferreiro, Ricardo M.; Garcia, Francisco; Garcia, Francisco; Moro, Enrique; Moro, Enrique; López, Lilia Rosa; López, Lilia Rosa (Centro Nacional de Educación Sexual, 1995)
Explicación de los fines de la planificación familiar. También se expone el proceso de dar a luz en las mujeres.